Implementasi Kemampuan Bahasa Anak melalui Literasi Sains dengan Menggunakan Metode Eksperimen di RA Al Inaroh Pasinan Lekok Pasuruan (PROCEEDING: The Annual International Conference on Islamic Education, 2019)
This research is motivated by the results of observations in RA Al Inaroh Pasinan Lekok Pasuruan, that early childhood scientific literacy skills are still low. One of the causes of this condition is because teachers do not optimize learning media in improving aspects of cognitive development, especially in scientific literacy.The purpose of this research is to develop scientific literacy skills of early childhood in learning activities through storytelling methods using basic color media. In addition, this research was carried out to be able to describe the process and improvement of the application of storytelling methods using basic color media.The subjects of this study were group A children with 19 children. This research was conducted using a class action research method with John Elliot's design carried out in three cycles and three actions in each cycle.The instruments used in this study were performance appraisal instruments using three indicators, observation sheets, field notes, tests, and documentation of activities in the form of photographs. Based on the research data obtained, it can be stated that efforts to improve early childhood scientific literacy skills through the method of storytelling using basic color media have succeeded in increasing.The success can be seen from the results of the average score obtained by the child in each cycle. In the first cycle the average score obtained was 2.2. Cycle II the average score obtained by children is 2.99. And in cycle III the child gets an average score of 3.48. From the results of the increased average score, this study can be an alternative to improve early childhood scientific literacy skills.